Perhitungan Jumlah Kendaraan Bermotor Dengan Metode Manual Traffic Counting Di Jalan Jenderal Sudirman Kota Pekanbaru - Syarah Adriana; Aryo Sasmita; Muhammad Reza (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Increasing population affect the mobility of transportation which has an impact on amount of vehicle but its not accompanied by the road capacity. This research is located on Jenderal Sudirman street, that has highest number of vehicle in Pekanbaru. This research intended count the vehicle amount in research location using manual method (traffic counting) to calculate the vehicle amount. The data collected directly at two (2) different points in Jendral Sudirman Street Pekanbaru, Point a is located in front of Sudirman Square dan point b is located in front of Ramayana Sudirman. The result showed the peak hour in point a and point b happen in afternoon (16:30-17:30) and the highest amount of vehicle occurs at point a, cause by difference conditions at the research location.Keywords: Carbon Monoxide Emissions, Vehicle amount, Speed of Vehicle